2002
DOI: 10.1016/s0092-8674(02)00656-6
|View full text |Cite
|
Sign up to set email alerts
|

AtPIN4 Mediates Sink-Driven Auxin Gradients and Root Patterning in Arabidopsis

Abstract: In contrast to animals, little is known about pattern formation in plants. Physiological and genetic data suggest the involvement of the phytohormone auxin in this process. Here, we characterize a novel member of the PIN family of putative auxin efflux carriers, Arabidopsis PIN4, that is localized in developing and mature root meristems. Atpin4 mutants are defective in establishment and maintenance of endogenous auxin gradients, fail to canalize externally applied auxin, and display various patterning defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
712
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 766 publications
(738 citation statements)
references
References 35 publications
24
712
0
2
Order By: Relevance
“…The quantitative analysis of protoxylem phenotypes was performed on fuchsin‐stained roots as described (Bishopp et al ., 2011). Lugol staining for columella starch granules was carried out as described previously (Friml et al ., 2002). For the confocal laser scanning microscopy, a Zeiss LSM 780 microscope was used.…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative analysis of protoxylem phenotypes was performed on fuchsin‐stained roots as described (Bishopp et al ., 2011). Lugol staining for columella starch granules was carried out as described previously (Friml et al ., 2002). For the confocal laser scanning microscopy, a Zeiss LSM 780 microscope was used.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments with auxin transport inhibitors in Arabidopsis have demonstrated that the auxin movement from the shoot toward the root tip is responsible for lateral root development (Reed et al, 1998), while auxin movement away from the root tip is required for gravitropism and primary root elongation (Rashotte et al, 2000), although involvement of basipetal auxin transport in lateral root formation has also been discussed recently (Casimiro et al, 2001). Several genes involved in auxin transport, including the postulated efflux carriers of the pin family (Gälweiler et al, 1998;Mü ller et al, 1998;Friml et al, 2002aFriml et al, , 2002b, the auxin importer aux1 (Marchant et al, 1999), and the postulated efflux carriers pgp1, pgp2, and pgp19 (Noh et al, 2001), have been cloned recently in Arabidopsis. The maize ortholog of pgp1 is not expressed in roots (Multani et al, 2003).…”
mentioning
confidence: 99%
“…Researches on the function, expression pattern and location of recently isolated auxin carriers [18], [21][22][23], [26] have provided a great wealth of date for understanding the physiological role of auxin and polar auxin transport during plant development. Till now, around 8 different pin-like genes have been found in Arabidopsis genome and a few homologous genes from rice as well.…”
Section: Discussionmentioning
confidence: 99%
“…Agrobacterium strain LBA4404 and GV3101 were used for leaf disc transformation of Nicotiana tobacum cv Gx-1 and floral dip transformation of Arabidopsis thaliana C24 [27,28]. Brassica juncea and tobacco plants were grown in the green house with a 12 h light (26 ) and 12 h dark (20 ) period. Arabidopsis plants were grown in a phytotron in soil with a 16 h light (22 ) and 8 h dark (15 ) period.…”
Section: Bacteria and Plantsmentioning
confidence: 99%
See 1 more Smart Citation